2017
DOI: 10.1111/1744-7941.12142
|View full text |Cite
|
Sign up to set email alerts
|

Flexible working arrangements in residential aged care: applying a person–environment fit model

Abstract: Ensuring sufficient staff numbers to accommodate an increasing need for aged-care services is one challenge facing the residential aged-care sector. Human resources management (HRM) policy and practice need to explore ways flexible working arrangements can be utilised to improve recruitment and retention. This study applied a person-environment (P-E) fit model to understanding the role of flexible working arrangements in contributing to the successful operation of residential aged-care facilities in Victoria, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 38 publications
3
29
0
1
Order By: Relevance
“…The work-life interface is one aspect of PE fit (Galinsky & Bond, 2013) and this study demonstrates the potential influence of WFC Previous research has identified that managerial support is critical for employees to manage work-life interaction (Weale et al, 2017) as well as being an important contributor to safety climate (Cox & Cheyne, 2000). The present research found negative impacts of low managerial support may be amplified in the presence of an unsatisfactory work-life interface.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…The work-life interface is one aspect of PE fit (Galinsky & Bond, 2013) and this study demonstrates the potential influence of WFC Previous research has identified that managerial support is critical for employees to manage work-life interaction (Weale et al, 2017) as well as being an important contributor to safety climate (Cox & Cheyne, 2000). The present research found negative impacts of low managerial support may be amplified in the presence of an unsatisfactory work-life interface.…”
Section: Discussionsupporting
confidence: 55%
“…Previous research has found that workplace factors, including support from colleagues and managers and flexibility in shift scheduling, enabling workers to establish satisfactory work patterns, contribute to PE fit, leading to positive outcomes for both individuals and organizations (Beauregard, 2011;Weale, Wells, & Oakman, 2017). Due to enduring gendered patterns of work and care-giving, poor work-life fit is particularly problematic for women .…”
Section: Person-environment Fitmentioning
confidence: 99%
See 2 more Smart Citations
“…Women and working carers are disproportionately impacted by poor work‐life balance due to the persistence of gendered patterns of work and care giving, despite increased workforce participation by women . Previous research has found that workplace factors, such as good managerial support and flexibility in shift scheduling, help workers achieve satisfactory work‐life balance, contributing to a number of positive outcomes for both individuals and organizations …”
Section: Introductionmentioning
confidence: 99%